Current surgical management of metastases in the neck from mucosal squamous cell carcinoma of the head and neck. Issue 2 (February 2016) - Green, Ben; Bisase, Brian; Godden, Daryl; Mitchell, David A.; Brennan, Peter A.
Abstract: Neck dissection, which is an important method of treatment for metastases from mucosal (and other) squamous cell carcinomas (SCC) of the head and neck, is also useful for staging disease. Since its inception it has changed from a radical to a more conservative procedure, and vital structures are preserved wherever possible. Refinements in methods of imaging to assess involvement in the neck have encouraged alternative approaches that can improve outcomes and reduce morbidity. We look at the reported evidence for the surgical management of metastases in the neck from mucosal SCC.